Каскадний морозильний пристрій - Стручаєв, Микола Іванович; Стручаев, Николай Иванович; Struchaiev, Mykola; Олексієнко, Вадим Олександрович; Алексеенко, Вадим Александрович; Oleksiienko, Vadym; Петриченко, Сергій Володимирович; Петриченко, Сергей Владимирович; Petrychenko, Serhii; Верхоланцева, Валентина Олександрівна; Верхоланцева, Валентина Александровна; Verkholantseva, Valentyna (My University, 2019)
UK: Стаття присвячена технології виробництва заморожених продуктів та наведено запропонований нами каскадний морозильний пристрій, як варіант удосконалення холодильного технологічного устаткування для заморожування дрібноштучних продуктів у щільному зваженому шарі з використанням швидкого заморожування і подальшого тривалого низькотемпературного зберігання фруктової та овочевої продукції. RU: Статья посвящена технологии и оборудованию для производства замороженных фруктов. Предложена конструкция каскадного морозильного устройства, как вариант усовершенствования холодильного технологического оборудования для замораживания мелкоштучных продуктов в плотном взвешенном слое с использованием быстрого замораживания и дальнейшего длительного низкотемпературного хранения фруктовой и овощной продукции. EN: The article is devoted to the technology of frozen food production and presents the cascade freezer offered by us as an option for improving refrigeration equipment for freezing fine-grained products in a dense weighed layer using rapid freezing and subsequent long-term low-temperature storage of fruit and vegetable products. The purpose of this work is to analyze the process of fluidization and semifluidinization freezing of fine-grained products. The cascade freezer offered by us includes a download unit, a heat-insulated chamber for freezing products with a mesh conveyor, connected to the evaporator of the refrigeration unit through the low-temperature air distribution channels, the fan, the discharge window, a mesh hollow rotating drum sloping in front of the mesh conveyor. The transportation means is made in the form of a vibrotransporter with an eccentric mechanism and springs. The product to be frozen is continuously supplied by the boot knot to the mesh hollow rotary drum, simultaneously including the fan. A rotating motion and free fall of the product begins and a vigorous heat exchange with low-temperature air, which leads to the frosting of the outer layer. Then the product is poured onto the net vehicle where, under the action of the eccentric mechanism and the springs, its vertical and horizontal displacement begins and a fluidized bed is formed. The use of a cascade freezer due to the installation of a mesh hollow rotating drum, and a mesh conveyor in the form of a vibrotransporter with eccentric mechanism and springs, simplifies the design, reduces energy costs, improves the stability of the suspended product layer that is frozen, increases the heat transfer rate in the fluidized bed and productivity of the freezing process as a whole. Energy costs for the creation of a fluidized bed in comparison with mechanical throwing at the freezing of raspberries in 1,5 ... 3,5 times bigger.
Каскадное морозильное устройство
Cascade freezer
Keywords: каскадний морозильний пристрій; холодильне технологічне устаткування; заморожування дрібноштучних продуктів у щільному зваженому шарі; швидке заморожування; фруктова та овочева продукції